Protecting gauge symmetries in the dynamics of SU(3) lattice gauge theories - Emil Mathew; Indrakshi Raychowdhury (Communications Physics)
Abstract Quantum simulation of a lattice gauge theory demands imposing on-site constraints. Ideally, the dynamics remain confined within the physical Hilbert space, where all the states satisfy those constraints. For a non-Abelian gauge theory, implementing these local Gauss’ law constraints is non-trivial. The presence of noise in current quantum devices further complicates efforts to confine the theory to the physical Hilbert space. The SU(3) gauge theory, describing the strong interaction of nature contains 8 mutually non-commuting local constraints. An efficient Hamiltonian simulation for the same should preserve all of these simultaneously - which stands as a notoriously difficult task. In this work, we explore two symmetry protection protocols for simulating SU(3) gauge theory in 1+1 dimensions. The first protocol does not require the imposition of any local symmetry but relies on protecting global symmetries, which are Abelian within the preferred choice of framework, namely the loop-string-hadron framework. The second protocol employs a protection scheme that is local, Abelian, and generalizable to higher dimensions. The symmetry protection schemes presented here are important steps towards quantum simulating the full theory of Quantum Chromodynamics.